Photocatalytic degradation of amoxicillin, ampicillin and cloxacillin antibiotics in aqueous solution using UV/TiO2 and UV/H2O2/TiO2 photocatalysis - M., Chaudhuri; E.S., Elmolla (2010)

(untitled)
Degradation of amoxicillin, ampicillin and cloxacillin antibiotics in aqueous solution by TiO2 photocatalysis under UVA (365 nm) irradiation was studied. Enhancement of photocatalysis by addition of H2O2 was also evaluated. The results showed that no significant degradation occurred by 300-min UVA irradiation per se and pH had a great effect on antibiotic degradation. Photocatalytic reactions approximately followed a pseudo-first order kinetics and the rate constants (k) were 0.007, 0.003 and 0.029 min- 1 for amoxicillin, ampicillin and cloxacillin, respectively. Addition of H2O2 at ambient pH âˆ¼ 5 and TiO2 1.0 g/L resulted in complete degradation of amoxicillin, ampicillin and cloxacillin in 30 min. Dissolved organic carbon (DOC) removal, and nitrate (NO3-), ammonia (NH3) and sulphate (SO42-) formation during degradation indicated mineralization of organic carbon, nitrogen and sulphur. UV/H2O2/TiO2 photocatalysis is effective for degradation of amoxicillin, ampicillin and cloxacillin in aqueous solution. Â© 2009 Elsevier B.V. All rights reserved.